Left Atrial Appendage Morphology and Left Atrial Wall Thickness Are Associated with Cardio-Embolic Stroke - Adukauskaite, Agne (J Clin Med, 2020)
Background. New markers for stroke risk stratification in patients with atrial fibrillation (AF) are on demand. Hence, we aimed to investigate the association of left atrial appendage (LAA) and left atrium (LA) morphological parameters in patients with cardio-embolic (CE) stroke due to AF in comparison to controls without stroke. Methods: A retrospective analysis of cardiac computed tomography angiography (CTA) examinations performed between 2006 and 2017 for clinical indications in 158 patients (median age 65 (54–73) years, 48.7% females) was conducted: 56 patients with CE stroke were compared to 102 controls not differing in gender, body mass index (BMI) and CHA(2)DS(2)-VASc score. Results: On multivariable regression analysis adjusted for CHA(2)DS(2)-VASc score and LA diameter CE stroke was independently associated with the following parameters: windsock LAA type (OR 2.55; CI: 1.04–6.26, p = 0.041), a greater lobe number (OR 1.54; CI: 1.13–2.10, p = 0.006), a greater LAA ostium area (OR 1.88; CI: 1.38–2.55, p < 0.001) and a greater left atrium wall thickness (LAWT) in the middle and right part, measured along the anterior LA wall in the axial plane (respectively, OR 1.94; CI: 1.26–3.0, p = 0.003 and OR 1.57; CI: 1.07–2.31, p = 0.021). Conclusions: The windsock LAA type, a greater LAA lobe number, a larger LAA ostium and a greater LAWT are associated with CE stroke. These CTA parameters could improve risk stratification for thromboembolic stroke.